Mathematical learning attributes impacting students' performance in Sarawak - Ting, Jing Jing; Ahmad Tarmizi, Rohani (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
The purpose of the study is to examine the mathematics learning attributes in mathematics classroom at the secondary school level in Malaysia. Students’ responses related to mathematics learning attributes were sought. A survey was conducted using a set of questionnaire (62 items) among rural secondary school students in the state of Sarawak, Malaysia. Four hundred and fifteen responses were collected. Self-reported students’ achievement in school based assessment was used as the measurement of mathematics performance which later was collapsed into categorical variables. Logistics Regressions was used to examine the significant predictors contributed to mathematics performance. The study indicates Learning Styles and Teaching Practices are predictors of students’ higher achievement in mathematics while other learning attributes are in place. This finding concurred with other studies which stressed the importance of teaching strategies and practices in mathematics learning class. Mathematics teacher must adapt their teaching technique according to their students’ learning style preferences and beliefs on mathematics to improve learning. This study will contribute to rural school educational research. The findings in this study would expand the current body of knowledge and data about the importance of learning attributes in pedagogical context. The study provides valuable information to teachers and school administrative to create effective learning program matching the needs of the students.